Towards a unified shear-induced lift model for prolate spheroidal particles moving in arbitrary non-uniform flow - Cui, Yan; Ravnik, Jure; Hriberšek, Matjaž; Steinmann, Paul (Computers & Fluids, 2020)
The paper proposes a unified shear-induced lift force model which divides the lift force into four lift components arising from the spin tensor, the volumetric and the deviatoric parts of the rate of deformation tensor, and the inertia effect of the Stokes drag. This unified model is successfully simplified into a shear-induced lift model for prolate spheroidal particles moving in arbitrary flow conditions via analogy arguments. The simplified shear-induced lift model for prolate spheroidal particles is verified by comparing it with several established lift force models via simulation of a prolate spheroidal particle moving in the Poiseuille and lid-driven cavity flows. The computational results demonstrate that the present lift force model for prolate spheroidal particles is applicable in flow cases with streamwise and non-streamwise flow shear. The implementation of the simplified lift model leads to computational results with reasonably small difference to the results of the full lift model of Cui et al. [Int. J. Multiph. Flow, 111, 232–240 (2019)], with a significantly decreased computational cost, rendering it as suitable for the implementation in large scale Lagrangian particle tracking.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Lagrangian particle tracking; Prolate spheroidal particle; Saffman-type lift; Unified shear-induced lift